효율적 재난관리를 위한 방재자원 분류체계 구축에 관한 연구 - 이창희; 정우영; Chang-Yeol Lee; 강병화 (한국재난정보학회 논문집, 9(2), 2013)
최근 국내외적으로 자연 및 인적재난에 의한 피해는 매년 증가하고 있다. 이들 재난에 대한 피해는 완전히 방지할 수는 없으나 국가적으로 잘 준비된 예방 및 관리대책 수립에 의하여 막대한 인명 및 재산피해가 발생되는 경우에 이를 충분히 저감할 수 있다. 방재자원은 재난발생 시 투입되는 인력, 물자, 장비, 시설자원을 의미한다. 실제 재난발생 시 이들 자원의 신속하고 적절한 투입은 실제 그 재난을 최소화하는데 매우 중요한 요소이다. 그러나 현재 국내 방재자원의 경우, 적절한 방재자원 동원을 위한 기준이나 분류가 체계적으로 구성되어 있지 못한 상황으로 이로 인한 효과적인 자원관리 및 투입이 효율적으로 운영되지 못하고 있는 실정이다. 본 연구는 현행 국내에서 불규칙적으로 적재, 활용되고 있은 방재자원의 효율적인 동원체계 구축을 위한 초기단계의 연구로서 보다 효율적인 방재자원의 관리 및 운영을 위한 방재자원의 기능별, 역할별 분류를 구축하고 이를 제시 보다 효과적인 방재자원 관리 및 동원시스템을 구축하는 토대를 마련하고자 한다. The damage caused by natural and human disasters has been increasing year by year. While the damage from these disasters are unavoidable, reduction of damage level by proper establishment of control measures could be sufficiently achievable. Disaster prevention resources include resources introduced in the event of disaster, such as human, materials, equipments and facilities. Rapid yet proper inputs of these resources are the key factor to minimize any damages from the disaster. Currently, however, the standard and/or criteria for mobilization of the disaster prevention resources have not yet systematically established. Therefore, proper resource management as well as efficient resource input has not been in place. This research is an early stage construction of efficient mobilization resources, which had been irregularly loaded and applied before. Also this study has tried to provide a classification rule for efficient disaster prevention resource management and mobilization, and indeed, provide a foundation for efficient resource management system. KCI Citation Count: 1